IBN AL-MUWAQ AND HIS SAYINGS IN DOCUMENTING NARRATORS A COMPARATIVE STUDY - Ather Muhammad Khalaf, Dr. Esam Khalil Ebrahim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The noble Hadith had a prominent role in preserving the Islamic religion, and God had prepared people to defend this religion by preserving the Book of God and the Sunnah of the Messenger of God (He paid doubts about the Sunnah of his Prophet), And there are a number of imams who knew of his condition and became famous for their affairs, and the scholars mentioned that he only tells one of them with confidence, for it was among the blessings of God Almighty that we were among the students of the Prophetic Sunnah’s sciences, and whoever we loved the legacy of our ancestors in their service and conquered them for what they obtained From the reward and honor of that, we wanted to share them in some of their reward, and that our honor in serving the Prophet’s Sunnah through what they honored them with, so the reason for our selection of this tagged (Ibn Al-Muwaqq and his sayings in documenting narrators was a comparative study) because some of the people of the hadith did not transmit his sayings in the wound and amendment.